Telaah Karakteristik Tafsir Arab-Pegon Al-Ibriz - Abu Rohkmad (Balai Penelitian dan Pengembangan Agama Semarang, 2011)
Every time, a dialogue between the Quran and its readers happens; andthe long period process of such understanding has resulted thousands andtons of interpretation books (kitab tafsir). One of them is Tafsir al-Ibriz byK.H. Bisri Mustofa and is written in Arab Pegon (Javanese language andArabic letters). This article is discussing the characteristics of the book andits method. Using descriptive analytic and hermeneutic interpretative, the studygoes to the conclusion that the book is organized according to tahlili method,namely a method which explains Quranic verses words after words. Themeaning of the words is presented in makna gandul system (the meaning iswritten under the words) while the interpretation and explanation (tafsir) iswritten out of the main body text. In terms of characteristics, the way the Tafsir al-Ibriz explains the meaning of the Quran is considered as simple.The approach applied in the book doesn’t tend to a particular interpretation style because it combines some different styles according to the contextual meanings; and this book belongs to traditional and ma’tsur category.